2020
DOI: 10.1111/avsc.12485
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐based approach for modeling the distribution of montane forest vegetation in Taiwan

Abstract: Aims Climate shapes forest types on our planet and also drives the differentiation of zonal vegetation at regional scale. A climate‐based ecological model may provide an effective alternative to the traditional approach for assessing limitations, thresholds, and the potential distribution of forests. The main objective of this study is to develop such a model, with a machine‐learning approach based on scale‐free climate variable estimates and classified vegetation plots, to generate a fine‐scale predicted vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…We found that, unlike the general expectation in biogeographic studies that an island only contains a subset of genetic diversity from the mainland population, the genetic diversity of S. cerevisiae populations from Taiwan can be as diverse as those found in the Asia continent. The persistence of ancestral lineages may be a result of Taiwan being a high environmentally heterogeneous region (Ali 2018;Lin et al 2020) and its prolonged bioclimatic stability (Tsukada 1966) than that of nearby eastern China. Alternatively, the geographic scale for distinguishing island and mainland populations and the importance of habitat diversity may differ between microorganisms (Davison et al 2018) and other macro-organisms, such as animals and plants.…”
Section: Discussionmentioning
confidence: 99%
“…We found that, unlike the general expectation in biogeographic studies that an island only contains a subset of genetic diversity from the mainland population, the genetic diversity of S. cerevisiae populations from Taiwan can be as diverse as those found in the Asia continent. The persistence of ancestral lineages may be a result of Taiwan being a high environmentally heterogeneous region (Ali 2018;Lin et al 2020) and its prolonged bioclimatic stability (Tsukada 1966) than that of nearby eastern China. Alternatively, the geographic scale for distinguishing island and mainland populations and the importance of habitat diversity may differ between microorganisms (Davison et al 2018) and other macro-organisms, such as animals and plants.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al found the highest model quality for the RF and GAM algorithms when assessing the limitations of different species distribution models using the Azorean Forest as an example 29 . The RF is an ensemble machine-learning model that could handle data with multi-dimensional, non-linear relationships, high-order correlations, and missing values 30 . Additionally, the RF model is capable of avoiding the accuracy reduction problem caused by missing and noisy data in the training sample when predicting the relationship between a large number of predictor variables and the response variable 31 , attributes supporting the present study results.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Tapia et al (2005) introduced a confusion index calculated as the ratio between the membership values of the community with the highest prediction and that having the second highest value. Lin et al (2020) assigned predicted pixels to either the predicted forest type or to “mixed” or “uncertain”, classes based on predicted values for the 13 forest types modeled. Duff et al (2014) directly predicted the fuzzy membership value for each association mapped.…”
Section: Discussionmentioning
confidence: 99%